THE DYNAMICS OF DAIDZEIN CHEMICAL COMPOUND FROM YAM TUBER (Pachyrhizus erosus) TUBER AND ITS POTENTIAL IN MYOMETRIUM - Cicilia Novi Primiani; Umie Lestari; Mohammad Amin; Sutiman B. Sumitro (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2013)
Daidzein compounds dynamic and the effect of yam tuber (Pachyrhizus erosus (L)) Urb on myometrium rats model of estrogenic were investigated. Twentyfour of 5 months-old female Sprague Dawley rats were randomly assigned to three groups as followed, control, Daidzein administraton and yam tuber juice administration for 24 days. The administration of yam tuber juice were given by orally using a stomach with gavage tube in the morning. Every 8 h, the rats blood and urine were collected from tail until 24 h. The treatment were continued until 24 days. The result showed that the level of daidzein in blood and urine of rats that administratered by Yam tuber juice is lower than pure daidzein treatment rats every 8 until 24 hours of collection. The results demonstrated that the administration of yam tuber juice significantly myometrium proliferated in rats. It is assumed that genistein and quercetin is estrogenic as found in daidzein so that the miometrium is potentially more effecctive. This study suggest that phytoestrogen compound from Pachyrhizus erosus may offer a potential as natural estrogenic in women.